2022
DOI: 10.3310/nihropenres.13233.3
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the acceptability of total diet replacement and food-based low energy diets for type 2 diabetes remission amongst South Asians: a public and patient involvement activity

Abstract: Background: With type 2 diabetes prevalence rising, low energy diets (total diet replacement and food-based low energy diets) are increasingly used to induce weight loss and achieve diabetes remission. The effectiveness of these diets has been primarily tested in the UK white population but not in the south Asian population at high risk of diabetes. Obtaining the opinion of members of the community on what would constitute a culturally acceptable diet is essential for successful interventions aiming to achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
(1 reference statement)
1
2
0
Order By: Relevance
“…One of the major challenges in recruiting participants reported by the HCPs included hesitation towards undertaking total diet replacement for 12 weeks. This resonates with the findings of a prior study where there was low acceptance towards 12‐week total diet replacement for diabetes remission because of reasons such as the requirement of long‐term commitment and perceived need of solid foods to have a fulfilling diet 24 . The hesitation could be amplified especially with the availability of recent medications that can result in significant weight loss but with potential side effects 25 .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…One of the major challenges in recruiting participants reported by the HCPs included hesitation towards undertaking total diet replacement for 12 weeks. This resonates with the findings of a prior study where there was low acceptance towards 12‐week total diet replacement for diabetes remission because of reasons such as the requirement of long‐term commitment and perceived need of solid foods to have a fulfilling diet 24 . The hesitation could be amplified especially with the availability of recent medications that can result in significant weight loss but with potential side effects 25 .…”
Section: Discussionsupporting
confidence: 77%
“…This resonates with the findings of a prior study where there was low acceptance towards 12-week total diet replacement for diabetes remission because of reasons such as the requirement of long-term commitment and perceived need of solid foods to have a fulfilling diet. 24 The hesitation could be amplified especially with the availability of recent medications that can result in significant weight loss but with potential side effects. 25 However, highlighting that sustained remission is achievable through a structured diabetes remission programme, along with presenting supporting evidence from prior studies, 8,9 may help motivate potential participants.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research has looked at perspectives of people of South Asian ethnicity in dietary programmes and found similar results; individuals wanted multilingual support, peer support and help with challenges around social and cultural factors such as family dynamics 41–43. Furthermore, research exploring acceptability of TDR and low energy diets in South Asian populations found participants had a preference for culturally tailored low energy food-based diet and that spices needed to be included to support with their home culture 44…”
Section: Discussionmentioning
confidence: 93%
“…Codeveloping and evaluating tailored interventions which are more culturally acceptable may help to ensure LED interventions are accessible and acceptable to specific high-risk populations. 29 At the time of the interviews (week 12 CLED; week 28 ILED) 4 CLED participants (out of 40) and 7 ILED participants (out of 39) had withdrawn from the study. An important and acknowledged further study limitation is that we did not interview participants who dropped out during the intervention stage or who opted not to take part in the study, although two of the participants interviewed (one CLED; one ILED) did subsequently withdraw from the trial after interview and before the end of the full 52-week study period (see Table 2).…”
Section: Discussionmentioning
confidence: 99%